Editor's Note: ARTICLE DOWNLOADS AND ABSTRACT VIEWS OF NIJOTECH (Nigerian Journal of Technology, 2018)
.I am compelled again to update you on the article downloads and abstract views as published by AJOL on June 26th 2018. AJOL assigns DOIs to us for free and has been doing that for over three years now. The statistics shown in Figure 1 and Table 1 are evident that our visibility keeps growing. Did you notice the trend in the graph? Is it difficult to guess where the graph is headed? Table 1 lists all countries in the world and frequency of downloads of NIJOTECH articles. With our OJS being updated automatically on monthly basis by OpenJournalSystems® based in USA, we cannot expect less. And it was only two years ago that we signed in to be on their software update list. Though it came at some cost (TETFUND intervened), we are hoping to sustain the tempo. It is only when downloads increase that citations can increase too. Just like rains needs clouds.